2015
DOI: 10.1007/s11604-015-0431-4
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous bronchonodal fistula in adult patients: CT findings

Abstract: Bronchonodal fistula can occur as a complication of active pulmonary TB with TB lymphadenitis in adult patients, especially in the elderly. The fistulas usually involved the right side. The lobar bronchus was frequently involved on the right side and the main bronchus on the left side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
3
14
0
2
Order By: Relevance
“…It is important to mention the value of chest CT in the diagnosis of this condition. In a study by Park et al , the tomographic characteristics were described in seven patients with active pulmonary tuberculosis and adenobronchial fistula, concluding that the fistula occurs as a complication of extensive pulmonary tuberculosis with involvement of more than four lobes, occurring mainly in patients older than 72 years old and mainly involving the right bronchial side 3. In our case there is only involvement of RIL and the involvement was of both main bronchi in an immunocompetent patient.…”
Section: Descriptionsupporting
confidence: 44%
“…It is important to mention the value of chest CT in the diagnosis of this condition. In a study by Park et al , the tomographic characteristics were described in seven patients with active pulmonary tuberculosis and adenobronchial fistula, concluding that the fistula occurs as a complication of extensive pulmonary tuberculosis with involvement of more than four lobes, occurring mainly in patients older than 72 years old and mainly involving the right bronchial side 3. In our case there is only involvement of RIL and the involvement was of both main bronchi in an immunocompetent patient.…”
Section: Descriptionsupporting
confidence: 44%
“…Tuberculous bronchonodal fistula is formed by erosion of lymph nodes into adjacent airway through inflammation and necrosis. [ 14 ] Tuberculous bronchonodal fistula in adults is extremely rare, contrary to that in children. Park et al [ 14 ] have reported CT and clinical characteristics of tuberculous bronchonodal fistula in 7 adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] Tuberculous bronchonodal fistula in adults is extremely rare, contrary to that in children. Park et al [ 14 ] have reported CT and clinical characteristics of tuberculous bronchonodal fistula in 7 adult patients. In their study, all patients were over 70 years old without major immunosuppressive diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations